Philosophical Underpinnings of Social Insurance Mechanisms within the Framework of Health Insurance - Theta Murty; Sukarmi Sukarmi; Yenny Eta Widyanti; Amelia Sri Kusuma Dewi (Sriwijaya Law Review, 2024)
Indonesia, as a country that adheres to the concept of a welfare state, seeks to achieve social welfare development by implementing a national social security system, particularly health insurance, managed by the Health Social Security Administration Agency (BPJS). It is regulated in Article 19, paragraph 1 of Law No. 40 of 2004 concerning the National Social Security System (SJSN). The fundamental principles of social insurance include mandatory participation, equitable health coverage, and contributions proportional to income. The philosophical issue at hand is whether implementing health insurance via the social insurance mechanism effectively guarantees the interests of the community while upholding the values of welfare and justice, as prescribed by the concept of the welfare state. This paper analyses the philosophical foundation underlying social insurance as a mechanism for implementing health insurance in Indonesia. This study employs normative research methods, utilising legislation as the analytical starting point. A philosophical examination is necessary to understand why, after a decade of implementing national health insurance, the state's goal of achieving welfare and social justice in health services for Indonesian citizens remains unmet. This analysis seeks to identify new mechanisms to fulfil the goals outlined in Law No. 40 of 2004.